Fatal fungaemia due to Cryptococcus albidus in an elderly diabetic woman presenting with pleural effusion (2020)
This is a fatal case of fungaemia due to Cryptococcus albidus in an elderly woman with type 2 diabetes mellitus who presented pleural effusion as the only clinical presentation. Not only infections of the pleura are uncommon presentations of pulmonary cryptococcosis, but these infections due to non-C. neoformans species are extremely rare. This report places C. albidus on the growing number of disseminated mycosis-causing agents in diabetic patients.